PENGGUNAAN METODE ANALITICAL HIERARCHY PROCESS (AHP) DALAM SISTEM PENUNJANG KEPUTUSAN PENENTUAN SEKOLAH DASAR - Masshitah, Sari; Perangin-angin, Elvi Sunita (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Problems that often arise among parents to determine the best school for their children. In determining a decision, it takes a lot of factors that influence the decision making. Therefore, it is deemed necessary to identify various important factors and consider the level of influence of a factor with other factors before making a final decision. The criteria taken in this study are the school environment, school distance, quality of teaching and learning, and school facilities. The method used in the decision support system is the Analytical Hierarchy Process (AHP) method. Determining the level of priority among primary school selection criteria can be determined from the percentage level of assessment criteria. The results of ranking after using the AHP method are choice 1 SDN Setu 02, choice 2 Makassar SDN 02 choice 3 SDN BA 04, choice 4 SDN BA 01.